2015 IEEE International Conference on Robotics and Automation (ICRA) 2015
DOI: 10.1109/icra.2015.7139802
|View full text |Cite
|
Sign up to set email alerts
|

Tip-over prevention: Adaptive control development and experimentation

Abstract: Skid-steered, tracked, tele-operated robots are used to perform high-risk critical missions such as bomb disposal under conditions deemed too risky to send a human. Often the robots carry heavy payloads that raise their centers of mass, increasing the risk of tip-over. Since it is often not feasible to send a human to right a toppled robot, tipover is equivalent to mission failure. Hence, an autonomous behavior to prevent robot tip-over is desired. In this research, a simplified model of mobile robot dynamics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
1
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…To keep the tendon drive continuum in a fully driven state and to meet the need for even arrangement of tendons, the minimum number of tendons in the continuum part is three. The tendon routing of the tendon-driven continuum can be divided into parallel tendons and helical tendons [24]. When a parallel tendon is added so that the BFWL module has four parallel tendons, the degrees of freedom of the tendon-driven continuum do not increase [25,26].…”
Section: Design Of Leg-wheel Mechanismmentioning
confidence: 99%
See 2 more Smart Citations
“…To keep the tendon drive continuum in a fully driven state and to meet the need for even arrangement of tendons, the minimum number of tendons in the continuum part is three. The tendon routing of the tendon-driven continuum can be divided into parallel tendons and helical tendons [24]. When a parallel tendon is added so that the BFWL module has four parallel tendons, the degrees of freedom of the tendon-driven continuum do not increase [25,26].…”
Section: Design Of Leg-wheel Mechanismmentioning
confidence: 99%
“…When the target turning radius R b is obtained by using Equation (20), it can be brought into Equation (23) to obtain the implicit functions of θ i and ϕ i that satisfy the conditions. Then, the appropriate parameters of θ i and ϕ i are selected and brought into Equation (24), and the twisting speed w i of the i-th leg can be calculated.…”
Section: Kinematic Modeling Of Wheeled Motionmentioning
confidence: 99%
See 1 more Smart Citation
“…The robot has a microphone array on the top of the lift for speech recognition and sound source localization. The mobile base also has an inertial measurement unit (IMU) with rate gyros, accelerometers, and a magnetometer that can be used for navigation and tilt detection to avoid tipping and toppling [39]. The wrist has accelerometers that can be used for bump sensing, and the D345i has rate gyros and accelerometers useful for visual perception.…”
Section: G Stretch's Sensorsmentioning
confidence: 99%
“…Liu et al have reported a real-time tip-over avoidance algorithm, which makes the best of online change of tracked vehicle configuration and adjustment of onboard manipulator s' posture [19], [24]. Moreover, many other traditional algorithms (minimum distance method [26], adaptive control method [27], inverse motion method [28], genetic method [29] and neural network based on observer method Caron et al [10]) have been being applied in robot's tip-over avoidance.…”
Section: Introductionmentioning
confidence: 99%